Implantación de la contabilidad de costos y análisis financiero para el restaurant Mis Delicious de la ciudad de Cariamanga, provincia de Loja, periodo junio del 2016 - Vega Romero, Yolanda del Rocío (2018)
The present work was developed in compliance with the requirement to obtain the degree in Accounting and Auditing, with the purpose of consolidating the knowledge acquired at the National University of Loja. And also offer its owner a technical accounting contribution that allows you to obtain reliable information timely, to make the best decisions, aimed at increasing your economic profitability. In order to comply with the objectives set out in the research, an Accounts Plan and Accounts Manual was designed, according to the needs of the business; then proceeded to raise the initial inventory with respect to goods, rights obligations that the restaurant owns; subsequently, the accounting process was applied until the conclusion of the Financial Statements; Finally, the financial indicators of liquidity, activity, indebtedness and profitability were applied to know their real accounting situation. The accounting process implemented in the Restaurant My Delicious, allowed to have a system of Costs for Production Orders that facilitates knowing the unit cost of each kind of prepared dish and later determining its sale price; it also helped to know the economic situation in which it is currently, contributing in this way with a control tool, which will allow its owner to obtain truthful, timely and reliable information on the operations carried out; process to make decisions, the same as, facilitate the optimal management of their finances and can apply targeted strategies to increase profitability.